EFFECTIVENESS OF USING EDUCATIONAL GAMES IN ENGLISH VOCABULARY DEVELOPMENT (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2025)
This article explores the impact of educational games on the enhancement of vocabulary acquisition among English language learners. It presents a comprehensive analysis of various game-based learning strategies and their effectiveness in promoting engagement, motivation, and retention of new vocabulary. The authors review existing literature on game-based learning, highlighting the cognitive and social benefits that games offer in an educational context.